2022-RA-728-ESGO High expression of vacuolar-ATPase subunit ATP6V1B1 predicts a poor prognosis and correlates with cell cycle progression in epithelial ovarian cancer. (20th October 2022) - Yun, Hee; Han, Gwan Hee; Kim, Hyosun; Cho, Hanbyoul; Kim, Sunghoon; Kim, Jae-Hoon
Abstract : Introduction/Background: Vacuolar-ATPase subunit ATP6V1B1 belongs to the ATP6V1s which participates in the biological process of transporting hydrogen ions and are associated with various cancers in expression and clinicopathological features, while its role its role in epithelial ovarian cancer (EOC) has not been clarified yet. Therefore, in this study we aim to evaluate the function, molecular mechanism and clinicopathological significance of ATP6V1B1 in EOC. Methodology: Expression level of ATP6V1B1 was screened by RNA sequencing of 10 EOCs and normal epithelial ovarian tissues. Expression levels of functional role of ATP6V1B1 were respectively evaluated by immunohistochemistry staining of EOC, borderline, benign and normal epithelial tissues. Associations of clinicopathological features and prognosis with ATP6V1B1 in EOC patients were analyzed both our recruited cohort and GEO datasets. Also, the functional roles of ATP6V1B1 were evaluated in EOC cell lines. Results: ATP6V1B1 protein was elevated in EOCs according to a GEO and TCGA datasets. High mRNA and protein levels of ATP6V1B1 were observed in EOCs compared to borderline, benign and normal nonadjacent ovarian epithelial tissues ( p < 0.001). Importantly, high expression level of ATP6V1B1 was associated poor overall survival and disease-free survival compared with low expression of ATP6V1B1 in EOCs ( p = 0.006, p < 0.001, respectively), and was associated with platinum-based chemotherapy resistance ( p < 0.001). In vitro results also demonstrated the knockdown of ATP6V1B1 was associated with decreased cell proliferation and colony forming abilities supporting the oncogenic role in EOC. Also, cell cycle analysis revealed a higher proportion of cells in G1 phase after knockdown of ATP6V1B1 ( p = 0.003). Conclusion: Our study is the first work to identify an oncogenic role of ATP6V1B1 in EOC tissues and cell lines which may provide insights into the application of ATP6V1B1 as a novel predictor of clinical outcome and a potential therapeutic target in EOC patients.